Augmented Reality Technology in Designing Sign Language Learning Applications - sugeng, sugeng; Nizar, Taufiq Nuzwir; Nathanael, Bob (Jurusan Informatika Universitas Tanjungpura, 2024)
Sign Language Learning Application Using Augmented Reality Technology with Markerless Method. Communication is an essential need for humans in everyday life. Every individual needs communication to understand the intentions of others towards themselves and their environment. However, some individuals face difficulties in communicating, especially for those with physical disabilities such as the Deaf. One common alternative form of communication used by the Deaf is sign language. This research aims to create a sign language learning application that combines Google Speech voice recognition technology and Augmented Reality with the markerless method. This application converts sound into SIBI sign language movements displayed in the form of 3D animation through Augmented Reality. This application will be used by the general public as a tool in learning sign language. Based on the results of testing that has been done, the application successfully achieves the goals set, with the integration of Google Speech voice recognition and Augmented Reality markerless achieving a success rate of 77.5%.